2003
DOI: 10.1080/01902140303788
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Icam-1, McP-1, and Mip-2 Protein Secretion by Rat Pleural Mesothelial Cells Following Exposure to Amosite Asbestos

Abstract: Pleural inflammation is a sequela of exposure to toxic mineral fibers such as amosite asbestos. This inflammatory response involves the influx of leukocytes from the vasculature into the pleural space. Adhesion molecules such as intercellular adhesion molecule-1 (ICAM)-1 and chemokines such as monocyte chemoattractant protein-1 (MCP)-1 and macrophage inhibitory protein-2 (MIP)-2 are known to be important in pulmonary inflammation following inhalation of particulate matter. However, little is known about their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…MCP-1 also plays a role in recruitment of eosinophils to acute and chronic inflammatory sites [36]. Furthermore, some particles such as silica [37] and amosite asbestos [38] reportedly can induce MCP-1 in vitro and in vivo . Thus, our findings indicate that pulmonary exposure to carbon nano particles may induce MCP-1 expression in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 also plays a role in recruitment of eosinophils to acute and chronic inflammatory sites [36]. Furthermore, some particles such as silica [37] and amosite asbestos [38] reportedly can induce MCP-1 in vitro and in vivo . Thus, our findings indicate that pulmonary exposure to carbon nano particles may induce MCP-1 expression in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…Pleural mesothelial cells are another source for increased levels of PDGF-BB after asbestos exposure and injury. This suggests that PDGF-BB could act in an autocrine fashion to increase CCL2 expression in mesothelial cells (18,19). We have previously shown that macrophages engulf inhaled MWCNTs and then migrate to the pleura, where they accumulate beneath the mesothelium (8).…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 is considered to be a profibrotic chemokine, as it plays a role in stimulating fibroblasts to produce collagen by induction and activation of TGF-b1 (20). In addition, CCL2 is a potent chemoattractant produced by pleural mesothelial cells that induces the migration of macrophages to an area of inflammation and injury (19). Time course experiments demonstrated that CCL2 mRNA and protein were induced transiently by PDGF-BB, whereas NiNPs caused a sustained increase in CCL2 expression ( Figures E1 and E2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hill et al (2003) reported that amosite asbestos causes pleural inflammation by increased secretion of Intercellular Adhesion Molecule-1 (ICAM-1), Monocyte Chemoattractant Protein-1 (MCP-1) and Macrophage Inhibitory Protein-2 (MIP-2) in pleural lavage fluid as well as in vitro mesothelial cell culture (Hill et al, 2003). Recent studies from our group have also shown that human mesothelial cells acquire resistance to asbestos-induced toxicity via induction of one or more Epidermal Growth Factor Receptor (EGFR)-linked survival pathways (PI3K/AKT/ERK1/2) during Simian Virus 40 (SV40) transformation and carcinogenesis (Shukla et al, 2011).…”
Section: Introductionmentioning
confidence: 99%